Cognitive impairment and Alzheimer’s disease: Links with oxidative stress and cholesterol metabolism - Alejandra Sekler; José M Jiménez; Leonel Rojo; Edgard Pastene; Patricio Fuentes; et al (Neuropsychiatric Disease and Treatment, 2008)
Alejandra Sekler1,2, José M Jiménez2, Leonel Rojo2, Edgard Pastene3, Patricio Fuentes4, Andrea Slachevsky4, Ricardo B Maccioni1,21Center of Cognitive Neurosciences, International Center for Biomedicine (ICC), Santiago, Chile; 2Laboratory of Cellular, Molecular Biology and Neurosciences, Faculty of Sciences, Universidad de Chile, Santiago, Chile; 3Department of Pharmacy, Faculty of Pharmacy, University of Concepcion, Concepción, Chile; 4Unidad de Neurología Cognitiva y Demencias, Servicio de Neurología, Hospital del Salvador, Santiago, ChileAbstract: Oxidative stress has been implicated in the progression of a number of neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease and amyotrophic lateral sclerosis. We carried out an in-depth study of cognitive impairment and its relationships with oxidative stress markers such as ferric-reducing ability of plasma (FRAP), plasma malondialdehyde and total antioxidative capacity (TAC), as well as cholesterol parameters, in two subsets of subjects, AD patients (n = 59) and a control group of neurologically normal subjects (n = 29), attending the University Hospital Salvador in Santiago, Chile. Cognitive impairment was assessed by a set of neuropsychological tests (Mini-Mental State Examination, Boston Naming Test, Ideomotor Praxia by imitation, Semantic Verbal Fluency of animals or words with initial A, Test of Memory Alteration, Frontal Assessment Battery), while the levels of those oxidative stress markers and cholesterol metabolism parameters were determined according with standard bioassays in fresh plasma samples of the two subgroups of patients. No significant differences were observed when the cholesterol parameters (low-, high-density lipoprotein, total cholesterol) of the AD group were compared with normal controls. Interestingly, a correlation was evidenced when the levels of cognitive impairment were analyzed with respect to the plasma antioxidant capacity (AOC) of patients. In this context, the subset of subjects exhibiting cognitive impairment were divided into two subgroups according with their Global Dementia Scale performance: a subgroup with mild AD and a subgroup with moderate to severe AD. Significant differences in AOC were found between subgroups. The different correlations between cognitive impairment of subgroups of subjects with the oxidative stress profile are discussed in the context of AD pathogenesis.Keywords: oxidative stress, molecular biomarkers, cholesterol parameters, cognitive impairment, Alzheimer’s patients